Adherence factors of enterohemorrhagic Escherichia coli O157:H7 strain Sakai influence its uptake into the roots of Valerianella locusta grown in soil. (December 2018) - Eißenberger, Kristina; Moench, Doris; Drissner, David; Weiss, Agnes; Schmidt, Herbert
Abstract: Increasing numbers of outbreaks caused by enterohemorrhagic Escherichia coli (EHEC) are associated with the consumption of contaminated fresh produce. The contamination of the plants may occur directly on the field via irrigation water, surface water, manure or fecal contamination. Suggesting a low infectious dose of 10 to 10 2  cells, internalization of EHEC into plant tissue presents a serious public health threat. Therefore, the ability of EHEC O157:H7 strain Sakai to adhere to and internalize into root tissues of the lamb's lettuce Valerianella locusta was investigated under the environmental conditions of a greenhouse. Moreover, the influence of the two adherence and colonization associated genes hcpA and iha was surveyed regarding their role for attachment and invasion. Upon soil contamination, the number of root-internalized cells of EHEC O157:H7 strain Sakai exceeded 10 2  cfu/g roots. Deletion of one or both of the adherence factor genes did not alter the overall attachment of EHEC O157:H7 strain Sakai to the roots, but significantly reduced the numbers of internalized bacteria by a factor of between 10 and 30, indicating their importance for invasion of EHEC O157:H7 strain Sakai into plant roots. This study identified intrinsic bacterial factors that play a crucial role during the internalization of EHEC O157:H7 strain Sakai into the roots of Valerianella locusta grown under the growth conditions in a greenhouse. Highlights: E. coli O157:H7 strain Sakai can indeed colonize the roots of lamb's lettuce. The numbers of internalized bacteria exceeded the infectious dose for human disease. The virulence factors hcpA and iha are crucial for internalization into root tissue.